Integrated microRNA/mRNA expression profiling of the skin of psoriasis patients. Issue 1 (January 2020) - Delić, Denis; Wolk, Kerstin; Schmid, Ramona; Gabrielyan, Ogsen; Christou, Demetrios; Rieber, Kathrin; Rolser, Marcel; Jakob, Ines; Wiech, Franziska; Griesser, Manuela; Wohnhaas, Christian; Kokolakis, Georgios; et al.
Abstract: Background: Psoriasis is a chronic inflammatory disease characterized by demarcated, raised, and scaling skin lesions. It often serves as a model for immune-mediated disorders. Gene expression profiling of affected skin has allowed insights into psoriasis pathogenesis. However, the mechanisms leading to specific mRNA expression alterations in psoriasis are barely understood. Objectives: To perform integrated microRNA-mRNA expression studies of non-lesional, peri-lesional, and lesional skin from psoriasis patients. Methods: Cutaneous microRNA and mRNA expression profiles of 14 patients using Nanostring nCounter-technology and RNA sequencing as well as in vitro keratinocyte stimulation and qPCR studies. Results: Only 3.5 % of microRNAs manifested a robust gradual expression trend from non-lesional to paired lesional skin, with 61 % being upregulated and 39 % being downregulated. Relevance of these microRNA regulations was supported by their inverse association with 57 % of the mRNA species found to be regulated during psoriatic lesion development. Many of the involved mRNAs were downregulated and functionally related to keratinocyte metabolism, barrier function, and neuronal signaling, and were already regulated in peri-lesional skin. An integrated correlation analysis revealed a robust interaction for 134 microRNAs/mRNAs pairs. In vitro keratinocyte studies of selected microRNAs/mRNAs revealed regulations of all analyzed microRNAs in a psoriasis-like manner by IL-17A/TNF-α ( e.g . hsa-miR-23a-3p), IFN-γ ( e.g . hsa-miR-106a-5p/miR-17-5p), or IL-24 ( e.g . hsa-miR-203a-3p). Moreover, most of their predicted target mRNAs ( e.g . ID4, EPHB2) were respectively altered by the same cytokines. Conclusion: Our study suggests that, during development of psoriatic lesions, defined aspects of psoriasis pathogenesis are regulated by the action of microRNAs.